Reputation: 1249
Why do function composition (∘
) and application ($
) have the implementation as available in https://github.com/agda/agda-stdlib/blob/master/src/Function.agda#L74-L76?
Copied here for convenience:
_∘_ : ∀ {a b c}
{A : Set a} {B : A → Set b} {C : {x : A} → B x → Set c} →
(∀ {x} (y : B x) → C y) → (g : (x : A) → B x) →
((x : A) → C (g x))
f ∘ g = λ x → f (g x)
_∘'_ : ∀ {a b c} {A : Set a} {B : Set b} {C : Set c} →
(B → C) → (A → B) → (A → C)
f ∘' g = λ x → f (g x)
_$_ : ∀ {a b} {A : Set a} {B : A → Set b} →
((x : A) → B x) → ((x : A) → B x)
f $ x = f x
_$'_ : ∀ {a b} {A : Set a} {B : Set b} →
(A → B) → (A → B)
f $' x = f x
I initially thought the rationale behind this was that $
would be able to handle higher order types that $'
wouldn't be able to handle. For example, consider A=Nat, B=List, f is ::, where B depends on A. But after a lot of testing, I couldn't come up with an example that would show that the implementation of $'
is not sufficient. What scenarios does $
handle that $'
isn't able to handle? (Similarly, what scenarios does ∘
handle that ∘'
doesn't?
open import Agda.Builtin.Nat public
open import Agda.Primitive public
--data List {a} (A : Set a) : Set a where
-- [] : List A
-- _∷_ : (x : A) (xs : List A) → List A
data Vec {a} (A : Set a) : Nat → Set a where
[] : Vec A zero
_∷_ : ∀ {n} (x : A) (xs : Vec A n) → Vec A (suc n)
tail : ∀ {a n} {A : Set a} → Vec A (suc n) → Vec A n
tail (x ∷ s) = s
_$_ : ∀ {a b} {A : Set a} {B : A → Set b} →
((x : A) → B x) → ((x : A) → B x)
f $ x = f x
_$'_ : ∀ {a b} {A : Set a} {B : Set b} →
(A → B) → (A → B)
f $' x = f x
_∘_ : ∀ {a b c}
{A : Set a} {B : A → Set b} {C : {x : A} → B x → Set c} →
(∀ {x} (y : B x) → C y) → (g : (x : A) → B x) →
((x : A) → C (g x))
f ∘ g = λ x → f (g x)
_∘'_ : ∀ {a b c} {A : Set a} {B : Set b} {C : Set c} →
(B → C) → (A → B) → (A → C)
f ∘' g = λ x → f (g x)
Vecc : ∀ {a} → Nat → (A : Set a) → (Set a)
Vecc x y = Vec y x
data Pair {a b} (A : Set a) (B : A → Set b) : Set (a ⊔ b) where
_,_ : (x : A) → (y : B x) → Pair A B
-- Dependent Pair attempt
--fst : ∀ {a b} {A : Set a} {B : A → Set b} → Pair A B → A
--fst (a , b) = a
--
--f : Pair Nat $' Vec Nat
--f = _,_ zero $' []
--
--g : Pair (Pair Nat $' Vec Nat) $' λ x → Nat
--g = _,_ (_,_ zero $' []) $' zero
-- Some other attempt
--f : ∀ {a n} {A : Set a} → Vec A ((suc ∘' suc) n) → Vec A n
--f {a} = tail {a} ∘' tail {a}
-- Vec attempt
--f : ∀ {a} (A : Set a) → (Set a)
--f {a} = Vecc {a} (suc zero) ∘' Vecc {a} (suc zero)
--
--h = f Nat
--
--x : h
--x = (zero ∷ []) ∷ []
-- List attempt
--f : ∀ {a} (A : Set a) → (Set a)
--f {a} = List {a} ∘' List {a}
--
--g : ∀ {a} (A : Set a) → (Set a)
--g {a} = List {a} ∘ List {a}
--
--h = f Nat
--i = g Nat
--
--x : h
--x = (zero ∷ []) ∷ []
Upvotes: 3
Views: 1016
Reputation: 5406
One works with dependent functions, the other doesn't, as Andras Kovacs mentioned.
The important difference is that for non-dependent functions stronger proofs can be constructed. For example:
eq : {A B} -> f : (A -> B) -> x y : A -> x == y -> (f x) == (f y)
eq f x .x refl = refl
Here we can construct equality of f x
and f y
. But we can't do the same for dependent functions - because there is no way to prove B x == B y
. So there is only a weaker proof that f x
can be "cast" to f y
.
transport : {A} {B : A -> Set} -> f : (x : A -> B x) -> x y : A -> x == y -> f x -> f y
transport f x .x refl fx = fx
(Actually, transport
is usually defined as B x -> B y
, not for a dependent function; but I just can't come up with a better name)
Upvotes: 0
Reputation: 30103
∘′
and $′
don't work with dependent functions. You simply didn't try any tests with dependent functions. For f $ x
examples, f
must be dependent, for f ∘ g
, either of the functions must be dependent. Example:
open import Data.Nat
open import Data.Vec
open import Function
open import Relation.Binary.PropositionalEquality
replicate' : {A : Set} → A → (n : ℕ) → Vec A n
replicate' a n = replicate a
refl' : {A : Set}(a : A) → a ≡ a
refl' a = refl
-- fail1 : Vec ℕ 10
-- fail1 = replicate' 10 $′ 10
ok1 : Vec ℕ 10
ok1 = replicate' 10 $ 10
-- fail2 : ∀ n → replicate' 10 n ≡ replicate' 10 n
-- fail2 = refl' ∘′ replicate' 10
ok2 : ∀ n → replicate' 10 n ≡ replicate' 10 n
ok2 = refl' ∘ replicate' 10
Upvotes: 4